2018
DOI: 10.1192/bja.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Family psychoeducation for people living with schizophrenia and their families

Abstract: SUMMARYMost people with schizophrenia have frequent contact with their families. Therefore, the family should be involved in their relative's treatment and care wherever possible, so that they can contribute to that person's recovery and the family's own needs for information, support and treatment can be addressed. Family psychoeducation refers to a group of structured psychotherapeutic interventions that involve the person with schizophrenia and their family as partners in care. Trained practitioners adopt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…12 Other reasons include funding and staff shortages, as well as providing necessary training. 13 In Japan, even if healthcare professionals perform FPE for a family, they cannot obtain reimbursement for medical expenses. In addition, while the Meriden Family Programme appears to be effective, training is time consuming and expensive.…”
Section: Open Accessmentioning
confidence: 99%
“…12 Other reasons include funding and staff shortages, as well as providing necessary training. 13 In Japan, even if healthcare professionals perform FPE for a family, they cannot obtain reimbursement for medical expenses. In addition, while the Meriden Family Programme appears to be effective, training is time consuming and expensive.…”
Section: Open Accessmentioning
confidence: 99%
“…Penelitian lain juga menunjukkan hasil yang sama dimana kecemasan dan persepsi beban keluarga menurun setelah diberikan psikoedukasi keluarga (Rosmaharani, Wihastuti, & Supriati, 2015). Penelitian pada klien skizofrenia menunjukkan bahwa psikoedukasi keluarga mampu meningkatkan pengetahuan keluarga, mengurangi gejala, mengurangi beban keluarga, meningkatkan kualitas hidup klien dan keluarga, serta mengurangi tingkat kekambuhan (Harvey, 2018;Hasan, Callaghan, & Lymn, 2015;Liza, Loebis, & Camellia, 2019).…”
Section: Pembahasanunclassified
“…Although initial FPE and support studies in the 1980s and 1990s indicated the primary goal of this treatment was to decrease high expressed emotion, 126 recent adaptations move toward a CBT-based model of providing family members with coping, communication, and problem-solving skills. 127 Additionally, recent literature review suggests pairing supportive interventions from both professionals and family members with lived experience (eg, NAMI) may provide the most overall benefit.…”
Section: Provide Family Psychoeducationmentioning
confidence: 99%